An Investigatory Project of Lemongrass (Cymbopogon citratus) as Scented Gel and Mosquito Repellent: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The Philippines is a tropical country and is home to thousands of species of flowering plants,including lemongrass, or tangled, in the local name, and typically used in cooking. Accordingto research, lemongrass can repel mosquitoes, which are most likely to grow and dissipate intropical countries. Because of the weather pattern in the Philippines, one of the commoncrises in the country is a vector-borne disease, an illness that results from an infectiondisseminated to humans by blood-feeding arthropods. To address the aforementioned issues,the usage of lemongrass as a natural repellent and scented gel could be a solution to reducethe use of synthetic mosquito repellent.The study's findings determine the degree of acceptability of lemongrass as scented gel andmosquito repellant in terms of materials, procedural methodology, effectiveness, eco-friendlyaspects, and presentation. Chemical engineers' overall weighted mean score was 3.41, whichis interpreted as “Highly Acceptable,” while environmental engineers’ score was 3.41, alsointerpreted as “Highly Acceptable”. There is no significant difference between the two sets ofengineers since the acquired t-computed is 0.000 and is less than the acquired t-critical valueof 0.706. The study's findings determine the degree of acceptability in terms of cost, scent,effectivity, appearance, and user-friendliness. Low-income families overall weighted meanwas 3.29, which is interpreted as “Highly Acceptable,” while the high-income families acquiredan overall mean of 3.33, interpreted as “Highly Acceptable.” There is no significant differencebetween the two sets of families since the obtained t-computed is 0.139 and is less than theacquired t-critical value 2.306.For further enhancement of the product, the two different sets of groups of respondentsrecommended and suggested an enhanced and strong scent, a more balanced formulation,enhanced effectivity to a wide range, and improved repellency endurance. In terms of theproduct’s container, it is recommended to make it recyclable and reusable. It is also advised tomake sure that a child cannot easily open the product's container.
Keywords: Engineering